A Study on Tourism Students' Communication Skills: Afyon Kocatepe University Example - PELİT, Elbeyi (Gaziantep University, 2018)
Today, as in every business, human resources is also very important in the labor intensive tourism sector. Providing and improving communication skills of tourism students who continue their vocational training is an important issue in the educational process. In this context, determining communication skills of the people in this process is important. The purpose of this research is to determine the graduate-level tourism students' communication skills. In this context, this research was carried out to the undergraduate level students studying at Afyon Kocatepe University Faculty of Tourism on 2014-2015 academic year spring semester. Survey method was used as a data collection method and 345 students participated to the research. According to the results of the study, students' communication skills were found to be generally high. Also according to the findings, female students have higher communication skills than male students